Media Pembelajaran Learning Media for Suku Anak Dalam Folklore Using the iSpring Suite Application in Inclusive Education - Rustam; Hary Soedarto Harjono; Priyanto; Lusia Oktri Wini (Journal for Lesson and Learning Studies, 2026)
The limited availability of interactive learning media and the lack of integration of local wisdom have led to low student interest and ability in understanding the elements and cultural values of Suku Anak Dalam (SAD) folklore. This condition is further complicated in inclusive schools with diverse student characteristics. This study aims to develop, test the feasibility, and evaluate the effectiveness of SAD folklore learning media based on the iSpring Suite application in improving students' understanding of story-building elements and local cultural values. The study used the Research and Development (R&D) method with the ADDIE model involving junior high school teachers and students at an inclusive one-roof school in Tebo Regency. Data were collected through a Likert-scale questionnaire (15 items), semi-structured interviews, and validation by material experts and media experts. Data analysis was carried out quantitatively through feasibility percentages and qualitatively using thematic analysis. The results showed that the developed media was categorized as very feasible based on expert validation (average >4.5) and very practical in implementation (average 4.74). The use of the media increased students' motivation, engagement, and ability to identify and describe character values in SAD folklore. This study concludes that the integration of digital-based SAD folk tales effectively supports literary learning in inclusive education and has implications for strengthening local cultural literacy.